Mathematical modeling of the migration process of components of phosphogypse dump in the environment - Chernysh, Yelizaveta Yu.; Plyatsuk, Leonid D. (Journal of the Belarusian State University. Ecology, 2018)
Тhe paper focused on identifies the main factors influencing the process of heavy metals migration in the environment from an array of phosphogypsum dumps. The mathematical modeling and description of the arrival of the stocks of plumbum from the dump into the soil were carried out. The graph of the evolution of the depth of occurrence of the "center of mass" of the vertical distribution of plumbum in the soil was presented according to the experimental and calculated data. The results of the investigation indicated a fairly slow shift in the plumbum concentration deep into the soil profile. It can be caused by the influence of several factors on the vertical migration of this element. In particular, the influence on its transformation in the ecosystem of the buffer properties of the soil complex and include of metal from phosphogypsum dump in poorly soluble form. The value of the directional transfer coefficient w = 0,19 cm / year was obtained in the work, which corre-sponds to the calculated value of the stocks of plumbum.
Keywords: migration depth; heavy metals; phosphogypsum dumps; modeling